Exploration Study of Organizational Support on Employees During the Covid-19 Pandemic - Imania Tami Shabrina; Rezki Ashriyana Sulistiobudi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The emergence of the coronavirus (COVID-19) pandemic that has occurred has had an impact on people's lives and has even changed the world economic order, one of which is the current industrial situation. The purpose of this study was to find out how the description of organizational support for employees’ welfare during the COVID-19 pandemic changed. The method used is qualitative research with an exploratory type. In this study, there are 10 respondents to be interviewed by researchers who work for the company. Focus Group Discussion is done by making a list of questions as a basis for collecting data. The results of the study show that organizational support during the pandemic is implementing health protocols, supervisor support, changing policies on how to work, and handling the organization for employees infected with COVID-19. The support provides positive emotions for employees, such as feeling safe and grateful. This allows employees to stay productive at work during the pandemic.